Spatially distributed channel shortening aided physical layer security - Solaija, Muhammad Sohaib J.; Salman, Hanadi; Qaraqe, Khalid A.; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers Inc., 2023)
Wireless networks have become imperative in all areas of human life. As such, one of the most critical concerns in next-generation networks is ensuring the security and privacy of user data/communication. Cryptography has been conventionally used to tackle this, but it may not be scalable (in terms of key exchange and management) with the increasingly heterogeneous network deployments. Physical layer security (PLS) provides a promising alternative but struggles when an attacker boasts a better wireless channel as compared to the legitimate user. In this work, a spatially distributed channel shortening approach is leveraged to address this problem. Specifically, the user data is split into multiple parts, where each part is sent using a different transmission point. This ensures that at least one of the illegitimate links experiences worse propagation channel as compared to the legitimate one. Additionally, a channel shortening filter is applied w.r.t legitimate links, which results in inter-symbol interference being introduced at the receiver. Results show significant enhancement of the achievable secrecy capacity as compared to state-of-the-art channel shortening-based PLS methods.
Keywords: 5G; 6G; Channel Shortening; Coordinated Multipoint (CoMP); Multi-Connectivity; OFDM; Physical Layer Security; Spatially Distributed System